SIMILARITIES AND DIFFERENCES FROM THE EUROPEAN EXPERIENCE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The agricultural situation that many developing countries are currently experiencing has similarities to the situation found in Europe after World War II when there was only limited uptake of newly available technologies, despite the fact that food...